2018
DOI: 10.1093/jtm/tay064
|View full text |Cite
|
Sign up to set email alerts
|

Does the DOSPERT scale predict risk-taking behaviour during travel? A study using smartphones

Abstract: In our study, individual scores on risk-taking in the health and safety subdomain of the DOSPERT questionnaire seem to be predictive of health behaviours both during travel and at home. By pairing new methods of data collection with questionnaires such as DOSPERT that identify key traveller characteristics to intervene on, travel medicine doctors will be able to provide more specialised health advice, ensuring that all travellers receive well-rounded advice about the full range of health challenges they will f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 21 publications
1
26
1
Order By: Relevance
“…71,85,86 More research is needed to establish the most promising uses of these data for travel health, and the combination of information extracted from traditional and innovative data sources are beginning to be produced and yield a proof of concept and road map for future studies on individual's risk assessment in travel medicine. [43][44][45] For instance, phylogeographic analyses can relate travel and epidemiological dynamics by integrating mobile data with expanding genetic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71,85,86 More research is needed to establish the most promising uses of these data for travel health, and the combination of information extracted from traditional and innovative data sources are beginning to be produced and yield a proof of concept and road map for future studies on individual's risk assessment in travel medicine. [43][44][45] For instance, phylogeographic analyses can relate travel and epidemiological dynamics by integrating mobile data with expanding genetic data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, prior research suggests that participants may be more likely to share sensitive or socially unacceptable information on an online form, improving understanding of rates of risky behaviours during travel. 72 Farnham et al [42][43][44][45] used mHealth technology to identify the range of health outcomes during travel using real-time monitoring and daily reporting of health behaviours and outcomes and identify traveller subgroups who may benefit from more targeted advice before and during travel. In this mHealth-based study, non-infectious disease-related health issues were commonly found in travellers, despite being largely unaddressed in traditional travel medicine research; in addition, clear patterns of traveller behaviour and health outcomes emerged, suggesting that subgroups of travellers exist for whom specialized medical advice is needed.…”
Section: Mhealth Applications and Risk Assessment In Travellersmentioning
confidence: 99%
See 1 more Smart Citation
“…This could imply that these methods of communication could be used for future (intervention) strategies as mobile technology will impact travel medicine more and more. 43–45 …”
Section: Discussionmentioning
confidence: 99%
“…Asking about behavioural patterns at home can help to identify people who are at special risk, as the DOSPERT questionnaire indicated in the Thailand study. 8 …”
Section: Innovative Researchmentioning
confidence: 99%